Cold-Water Immersion Versus Passive Therapy to Decrease Delayed Onset Muscular Soreness: A Cat [Comparación Entre Inmersión en Agua Fría y Terapia Pasiva Para Disminuir el Dolor Muscular de Inicio Tardío: Cat] - Aguilera-Eguia, R (2014)
INTRODUCTION: Late onset muscle soreness, also known as delayed onset muscle soreness, is a painful musculoskeletal condition that may occur 24-48 and up to 72 hours after the completion of unusual physical or high intensity exercise involving eccentric muscle activity. In the field of physical rehabilitation, immersion in cold water is a common intervention mainly used in sports medicine, to minimize delayed onset muscle soreness and promote recovery after exercise.OBJECTIVES: To assess the validity and applicability of the results regarding the effectiveness of immersion in cold water after high intensity exercise and answer the following question: In subjects who exercise regularly, can cold-water immersion compared to passive therapy (rest) reduce late-onset muscle soreness?METHODS: The article "Cold Water Immersion (cryotherapy) for preventing and treating muscle soreness after exercise," a Cochrane systematic review authored by Bleakley et al (2012), was analyzed.RESULTS: Immersion in cold water can decrease delayed onset of muscle pain after high intensity exercise. Twenty-four hours after the intervention, the mean standardized difference was -0.55 (95% CI: -0.84 to -0.27); 48 hours after, the mean standardized difference was -0.66 (95% CI: -0.97 to -0.35); 72 hours after, the mean standardized difference was -0.93 (95% CI: -1.36 to -0.51) and up to 96 hours after, mean standardized difference was -0.58 (95% CI: -1.00 to -0.16).CONCLUSION: Despite the methodological limitations present in the studies included in the systematic review analyzed, we found the recommendation for cold water immersion (cryotherapy) reasonable in individuals with late muscle pain caused by high intensity sports.Abstract available from the publisher.